Equal treatment for all workers: an analysis of the termination of employment probation contracts - Omurunga, A. O. (Strathmore University, 2024)
The employees on probationary contracts are not protected very well under the Kenyan legal framework because the denies them from the fundamental rights like a fair hearing a fair labor practices which are guaranteed by the Constitution, the Termination of Employment Convention and the Employment Relationship Recommendation which advocate for equality of all employees including those ones under probationary contracts. The existing provisions concerning the dismissal of probationary employees as outlined in the Employment Act of 2007 have raised concerns, as they allow employers to terminate the employment of probationary staff without providing them with essential rights like providing a chance to present their case, claiming that their employment contracts were unfairly terminated and an opportunity to lodge a complaint for unfair dismissal. Moreover, although the probationary period is intended to assess the employee's suitability for long-term employment, the existing legal framework lacks established criteria for evaluating suitability during this period. Instead, the determination is solely at the discretion of the employer, who may set challenging standards for employees to meet during their probationary tenure. As a result, employees on probationary employment contracts are denied essential rights that are provided by the 2010 Constitution and international conventions. Furthermore, the employers are granted more powers to determine the suitability of the probationary employees and they can terminate the contracts of probationary employees without being reprimanded by the law. It is for these reasons that there is a need for change in the current legal framework to promote the equality to employees on employment contracts and probationary employment contracts and reduce the powers the employers have over the employees.
Full - text undergraduate research project